Biomonitoring of aquatic pollution: status and trends from genomics to populations - Olanike K. Adeyemo; Temitope O. Sogbanmu; Selim A. Alarape; Nancy D. Denslow (The Proceedings of the Nigerian Academy of Science, 2020)
Biomonitoring offers an appealing tool for the assessment of pollution in aquatic ecosystem. Biological processes, species, or communities of bioindicators are used to assess the quality of the environment and how it changes over time. Bioindicators include algae, macrophytes, zooplanktons, insects, bivalves, molluscs, gastropods, fish, amphibians, and others. Changes in aquatic ecosystems are often attributed to anthropogenic disturbances, including pollution. Major contributors to aquatic pollution include wastewater, metals and metalloids, industrial effluents, contaminated sediments, nutrients, polycyclic aromatic hydrocarbons, flame retardants, persistent organic pollutants, pharmaceuticals and illicit drugs, emerging contaminants (such as microplastics and engineered nanoparticles), pesticides, herbicides, and endocrine disruptors. In this review, we discuss categories of aquatic pollutants, status and trends of aquatic biomonitoring and approaches, from genomics to populations. We conclude by offering recommendations for research and regulatory testing.